2020
DOI: 10.1096/fasebj.2020.34.s1.06164
|View full text |Cite
|
Sign up to set email alerts
|

Histone Deacetylase Inhibitors Enhance CRISPR‐Cas9 Cutting Efficiency

Abstract: The CRISPR/Cas9 technology is a prominent genome‐editing tool as an adaptable nuclease capable of producing a double strand break at almost any genomic loci. However, the modification of hematopoietic stem and progenitor cells (HSPC) via the homology directed repair (HDR) pathway is still inefficient. We hypothesize that histone deacetylase inhibitors (HDACi), such as Valproic Acid (VPA) and Sodium Butyrate (NaB), could enhance HDR efficiency by increasing the accessibility of the genome‐editing machinery. To … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…It has been reported that treatment with the histone deacetylase inhibitor VPA increases the genome editing efficiency in mouse embryonic stem cells and embryos [42]. In addition, the positive effect of NaB as well as VPA on CRISPR/Cas9 cutting efficiency has been reported in hematopoietic stem and progenitor cells [43]. Other HDAC inhibitors as well as TSA appear to play a positive role in the genome editing process in plant cells.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that treatment with the histone deacetylase inhibitor VPA increases the genome editing efficiency in mouse embryonic stem cells and embryos [42]. In addition, the positive effect of NaB as well as VPA on CRISPR/Cas9 cutting efficiency has been reported in hematopoietic stem and progenitor cells [43]. Other HDAC inhibitors as well as TSA appear to play a positive role in the genome editing process in plant cells.…”
Section: Discussionmentioning
confidence: 99%